2001
DOI: 10.1111/j.1365-2516.2001.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of chronic myelomonocytic leukaemia and factor XI deficiency with a circulating anticoagulant

Abstract: Inhibitors against factor XI (FXI) have been frequently described in patients who acquired inhibitors (due to auto‐inmune disorders, malignancies or infections), but less often in those with a congenital deficiency of this factor, who had received plasma infusions. The present report concerns one such inhibitor found in the plasma of a patient with chronic myelomonocytic leukaemia and infected by B19 parvovirus, who was neither a heterozygote nor a homozygote for FXI deficiency, and who had no bleeding tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although several autoimmune disorders including autoimmune haemolytic anaemia, pure red cell aplasia, autoimmune immune neutropaenia and immune thrombocytopaenia are common paraneoplastic manifestations of lymphoproliferative disorders, autoimmune phenomena have been sporadically reported in patients with CMMoL. Furthermore, autoantibodies against circulating coagulation factors such as FVIII and factor XI in patients with CMMoL were previously reported [3,11]. These autoimmune disorders were able to be successfully treated with immunosuppressive therapy [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Although several autoimmune disorders including autoimmune haemolytic anaemia, pure red cell aplasia, autoimmune immune neutropaenia and immune thrombocytopaenia are common paraneoplastic manifestations of lymphoproliferative disorders, autoimmune phenomena have been sporadically reported in patients with CMMoL. Furthermore, autoantibodies against circulating coagulation factors such as FVIII and factor XI in patients with CMMoL were previously reported [3,11]. These autoimmune disorders were able to be successfully treated with immunosuppressive therapy [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The disorder is common among Ashkenazi Jews, in whom a nonsense mutation Glu117stop (termed type II mutation) prevails [6]. Inhibitors against FXI have been described in patients with autoimmune and malignant diseases [7–10] or as a rare complication of replacement therapy with fresh frozen plasma (FFP) in patients with severe FXI deficiency [11–15]. Recently it was suggested that FXI deficient patients homozygous for type II mutation are the most susceptible for inhibitor formation following exposure to FFP [16].…”
Section: Introductionmentioning
confidence: 99%